DESCRIPTION OF SPORT HABITS IN STUDENTS OF MEDICAL BACHELOR PROGRAM AND DOCTOR PROFESSION FACULTY OF MEDICINE UDAYANA UNIVERSITY, 2019/2020 AT THE TIME OF THE COVID-19 PANDEMIC - Holil, Felicia; Muliarta, I Made; Tirtayasa, Ketut; Griadhi, I Putu Adiartha (E-Jurnal Medika Udayana, 2021)
Non-communicable diseases such as diabetes mellitus and cardiovascular disease are currently becoming the leading cause of death in the world. It can be caused by lack of exercise. As a medical student, we are expected to success the Germas program, which includes sports habits so that medical students can later become examples and provide good consultation related to sports to reduce risk factors for non-communicable diseases. This study aims to determine the description of sports habits in students of the Undergraduate Medical Program and the Medical Profession of the Faculty of Medicine, Udayana University in 2019/2020. This study applied a descriptive quantitative method and a cross-sectional approach. There are 140  respondents collected in this study using a proportional stratified random sampling, consisting of the students of Undergraduate Program of Medicine and Doctor's Profession, Faculty of Medicine, Udayana University in 2019/2020 class of 2015-2019. International Physical Activity Questionnaire (IPAQ) is used to measure the exercise habits data. This study found 90.7% students of the Undergraduate Medical and Professional Doctor Study Program, Faculty of Medicine, Udayana University in 2019/2020 were accustomed to exercising, which mostly found in women (92%), had a BMI overweight (100%), very highly motivated (100%), and had more time availability (96.2%). The results of this study can be used as a basic data for further research, to find the relationship between exercise habits and students' physical fitness. Keywords: sports habits, physical activity, students